Draft Proposal for Comment: Etiquette Rules and Procedures for Unlicensed Bands - Bahl, Paramvir; Hassan, Amer; Devries, Pierre; Bahl, Victor (Open White Paper, Proposal to the Industry and the FCC, 2003)
This document is a draft for discussion of etiquette rules for short range wireless devices operating in the unlicensed frequency band. Regulators like the Federal Communications Commmission (FCC) can be invited to apply these rules to the operation of ‘unlicensed’ wireless devices. The wireless devices may support asynchronous and/or isochronous digital communications. The proposed set of rules builds on rules that govern operation of wireless devices in Europe [11] and Japan and enhances them for adoption in the United States. It is our belief that these rules will enable the regulators of our spectrum to set an etiquette that enforces fair sharing of our precious national resource, while still allowing people to innovate at all levels of the protocol stack.